Costo de producción de la Fresa y su incidencia en la rentabilidad por hectárea de los Agricultores Individuales de Chepén - 2018 - Saba Alvitres, Karla Noelia (2019)
The present work of investigation realized in the Sector of Irrigation Lurifico at the level of the Individual Farmers and located in the district of Chepén; Its purpose is to propose a design of Costs by Processes and to determine its Total Cost of Strawberry Production per hectare so that establishing its total investment or costing its profitability per hectare is determined and it is demonstrated to the Individual Farmer of the district of Chepén accustomed to of the total of agricultural hectares, 92% of its hectares sow only rice husk, which generates an over production of rice which harms them since the greater quantity produced under the price per kilogram of the husked rice generates low profitability to the individual farmer or he has to take the measure of hiding his rice crop until his price rises in the local or national market. In this sense, the present investigation proposes to substitute the planting of rice in fewer hectares and that in its replacement cultivate the strawberry as an alternative crop to establish its cost and profitability per hectare in Chepén; and at the same time, determine the different financial tools that allow an adequate administration of the economic and financial resources of the individual farmer. As research results it was determined that the total production cost for a hectare is S / 25,000 and it obtains a profitability of S /.35,000. And the average overall productivity of the strawberry is around 40,000 kg / ha with a maximum of 45,000 kg / ha and a minimum of 35,000 kg / ha, with a 5% error. When it goes down to 20,000 Kgr./ha. at that level the farmer does not lose but he does not win as he was expecting. Likewise the strawberry is a plantation so in the following five years the farmer will obtain a good profitability and their conservation and maintenance costs are less than their investment in the first year so it is a great alternative for the individual farmer to plant of strawberry in the California variety and Aroma.